1994
DOI: 10.1002/ijc.2910570710
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the neural cell adhesion molecule (NCAM) in serum of patients with small-cell lung cancer (SCLC) with “limited” or “extensive” disease, and bone-marrow infiltration

Abstract: The neural cell adhesion molecule (NCAM) is a tumourrelated antigen found on the surface of small-cell lung cancer (SCLC). NCAM exists in several molecular forms, including a soluble isoform. We have measured serum levels of NCAM using an enzyme immunoassay with 2 anltibodies, NCC-LU-246 and NCC-LU-243, that react with different epitopes on the NCAM molecule. NCAM activity from 83 patients with active SCLC, either pre-treatment, progressing oir in relapse was significantly higher than in 70 patients on follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…With regard to current biomarkers used in the clinic, this is the expected concentration range, giving us hope that new lung cancer markers should be detectable in serum. Through our method, we successfully identified proteins that are putative or currently used as biomarkers of lung cancer, including CEA (27,28), pro-GRP (29,31), SCC antigen (47,48), tumor M2-PK (49), NCAM (35)(36)(37), chromogranin A (29), and chromogranin B (30). In addition, we identified putative markers previously reported in lung-related proteomics studies such as member C1 of aldo-keto reductase family 1 identified by Huang et al (25) as dihydrodiol dehydrogenase and matrix metallopeptidase 1 found to be overexpressed in lung cancer patients and especially in late stage (18).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to current biomarkers used in the clinic, this is the expected concentration range, giving us hope that new lung cancer markers should be detectable in serum. Through our method, we successfully identified proteins that are putative or currently used as biomarkers of lung cancer, including CEA (27,28), pro-GRP (29,31), SCC antigen (47,48), tumor M2-PK (49), NCAM (35)(36)(37), chromogranin A (29), and chromogranin B (30). In addition, we identified putative markers previously reported in lung-related proteomics studies such as member C1 of aldo-keto reductase family 1 identified by Huang et al (25) as dihydrodiol dehydrogenase and matrix metallopeptidase 1 found to be overexpressed in lung cancer patients and especially in late stage (18).…”
Section: Discussionmentioning
confidence: 99%
“…Ectodomain shedding of cell adhesion proteins such as carcinoembryonic antigen (CEA) (33,34), NCAM (35,36), or CD44 (37, 38) is linked to strong overexpression of these proteins in certain types of epithelial cancers, and the soluble forms of these proteins may serve as clinical tumor markers. We found previously that the cell adhesion molecule L1 is overexpressed in some renal tumors (2).…”
Section: Discussionmentioning
confidence: 99%
“…it has been shown that the serum levels of polysialylated NCAM are elevated in adult patients with small-cell lung cancer (Jaques et al 1993) and multiple myeloma (Kaiser et al 1994). high levels being associated with a poor prognosis (Ledermann et al 1994: Smith et al, 1996.…”
mentioning
confidence: 99%